The epidemic of HIV infection and AIDS, promotion of testing, and innovative strategies - Barbara Suligoi; Mariangela Raimondo; Emanuele Fanales-Belasio; Stefano Buttò (Istituto Superiore di Sanità, 2010)
In Europe, the incidence of new diagnoses of HIV infection in 2008 was 86.7 cases per one million population, and most cases were attributable to sexual transmission. In Italy, in 2007, the incidence was 60.0 cases per one million population (in the areas in which surveillance exists), and 73.7% of the cases were attributable to sexual transmission. At present, there are an estimated 170 000-180 000 persons living with HIV/AIDS in Italy, some of whom are unaware of being infected. Based on available epidemiological data and taking into consideration the level of risk of exposure to HIV, we describe several proposals for promoting access to HIV testing in diverse population groups and contexts, including some innovative approaches. The promotion of HIV testing is fundamental for public health and human rights and must be associated with treatment, care and prevention activities, which must be guaranteed for the entire population.